العلاقة بين القيادة التحويلية والالتزام التنظيمي وأثرهما في الفاعلية التنظيمية (من وجهة نظر العاملين في الشركة العامة لكهرباء دمشق) - عواد, يونس; إبراهيم, قدري عثمان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدف البحث إلى معرفة مستوى القيادة التحويلية، والالتزام التنظيمي، والفاعلية التنظيمية في الشركة العامة لكهرباء دمشق، وتقصي العلاقة بين القيادة التحويلية والالتزام التنظيمي، وتحديد أثرهما في الفاعلية التنظيمية من وجهة نظر العاملين فيها.وفي سبيل تحقيق ذلك استُخدم المنهج الارتباطي، وصممت استبانه لجمع البيانات تكونت من (45) فقرة، وزعت (82) استبانة،استرداد منها (51) استبانة صالحة للتحليل الإحصائي.بينت النتائج أن القيادة التحويلية درجتها مرتفعة، حيث بلغ متوسطها الحسابي (4.696). وأن مستوى الالتزام التنظيمي للعاملين متوسط حيث بلغ متوسطه الحسابي (3.50).والمتوسط الحسابي للفاعلية التنظيمية (3.48) ويدل على درجة متوسطة.أشارت النتائج أيضاً أن هناك علاقة ذات دلالة إحصائية بين القيادة التحويلية والالتزام التنظيمي، كما تبين أن هناك أثر ذو دلالة إحصائية لكل منهما في الفاعلية التنظيمية.أوصى الباحث بتعزيز ممارسة القيادة التحويلية في الشركة المدروسة لما لها من دور في خلق الالتزام التنظيمي لدى العاملين، وذلك من أجل زيادة الفاعلية التنظيمية للشركة، الأمر الذي يمكن أن يرفع مستوى أداءها الاقتصادي والاجتماعي.The aim of this study was to identify the level of transformational leadership, organizational commitment, and organizational effectiveness. The study examines the effect of Transformational Leadership and Organizational Commitment on Organizational Effectiveness from the perspective of workers in Damascus Electricity General Company.In order to achieve these objectives the researcher used the Correlational Research approach. Questionnaire consisted of (45) items has designed to collect the primary data, it has been distributed to a sample of (82) employees, a (51) Questionnaires were analyzed by using the statistical program (SPSS).Findings indicated a high level of transformational leadership where the average (4.69), a medium degree of organizational commitment of workers where the mean value reached (3.50), the ratings of a sample of organizational effectiveness was medium where the average (3.48).The study concludes that there is a statistically significant effect of Transformational Leadership and Organizational Commitment on Organizational Effectiveness.The study recommended to increase the practice of Transformational Leadership. Because of its role in creating the organizational commitment of employees, in order to increase the level of organizational effectiveness of company, which will reflected on raising the level of company’ economic and social performance.